DEVELOPMENT OF LANGUAGE COMPETENCE OF FUTURE TEACHERS BY MEANS OF USING LINGUOGRAPHICAL APPROACH IN PRACTICAL CLASSES IN ENGLISH (Pedagogy of Higher and Secondary Education, 2010)
This article considers the problem of formation of the linguistics competence of future specialists in the context of realization of the country study approach on the polish practical lessons.
Keywords: professional competence; countrystudy approach